Discontinuously Reinforced Titanium Matrix Composites : Microstructure Design and Property Optimization - Huang, Lujun; Geng, Lin (Springer Singapore : Imprint: Springer, 2017)
This book introduces readers to titanium matrix composites (TMCs) with novel network microstructures. The bottleneck problem of extreme brittleness and low strengthening effect surrounding TMCs fabricated by means of powder metallurgy has recently been solved by designing network microstructures, which yield both high strength and superior ductility. As such, network structured TMCs will increasingly offer materials characterized by low weight, high strength, high temperature resistance and superior deformability. The book systematically addresses the design, fabrication, microstructure, properties, modification, and toughening mechanisms of these composites, which will help us find innovative solutions to a range of current and future engineering problems.
Keywords: Materials science.; Industrial engineering.; Metals.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books